Challenges of Skopje Green City – Establishing Green Corridors Upon the Rivers Lepenec and Serava - Penchikj, D. and Hadzi Pecova, S. (Faculty of Forestry in Skopje, Ss. Cyril and Methodius University in Skopje, 2018)
For years, the City of Skopje has been facing the problem of increasing pollution, congestion, uneven construction, but also the problem of losing free public spaces, especially green. Unfavourable environmental conditions and the diminished quality of life, is mostly reflected in health of residents, but also in their satisfaction of living in the city. The city is becoming an inconvenient and undesirable place to live not only from an environmental point of view, but also from a sociological and economic point of view. Within the last ten years, the City of Skopje has intensified its efforts to attain the status of Green City by adopting the United Nations recommendations for achieving the goals of sustainable development. This article presents the urban aspects that are part of the research and results of the Study on the development of green corridors along the rivers Lepenec and Serava. Green corridors have been recognized as important elements for the enrichment of the green infrastructure of the city, whose basic functions and goals are related to improving the quality of life, mitigating the effects of climate change, preserving biodiversity, increasing the diversity of opportunities in urban areas and establishing sustainable transport corridors.
Keywords: sustainable development, green city, green corridor